Central Facial Nervous System Biomolecules Involved in Peripheral Facial Nerve Injury Responses and Potential Therapeutic Strategies - Jae-Min Lee; You Jung Choi; Myung Chul Yoo; Seung Geun Yeo (Antioxidants, 2023)
Peripheral facial nerve injury leads to changes in the expression of various neuroactive substances that affect nerve cell damage, survival, growth, and regeneration. In the case of peripheral facial nerve damage, the injury directly affects the peripheral nerves and induces changes in the central nervous system (CNS) through various factors, but the substances involved in these changes in the CNS are not well understood. The objective of this review is to investigate the biomolecules involved in peripheral facial nerve damage so as to gain insight into the mechanisms and limitations of targeting the CNS after such damage and identify potential facial nerve treatment strategies. To this end, we searched PubMed using keywords and exclusion criteria and selected 29 eligible experimental studies. Our analysis summarizes basic experimental studies on changes in the CNS following peripheral facial nerve damage, focusing on biomolecules that increase or decrease in the CNS and/or those involved in the damage, and reviews various approaches for treating facial nerve injury. By establishing the biomolecules in the CNS that change after peripheral nerve damage, we can expect to identify factors that play an important role in functional recovery from facial nerve damage. Accordingly, this review could represent a significant step toward developing treatment strategies for peripheral facial palsy.